Ochratoxin-A and Mold in Some Broiler Farms of Ismailia, Egypt and Evaluation of Common Mycotoxin Binders - Hassan , Ahmed M.; Youssef, Ahmed I.; Reddy, Pochana G. (International Journal of Poultry Science, 2012)
Ochratoxin A (OTA) is a serious problem affecting the poultry industry as well as a health hazard for humans consuming contaminated poultry meat. The aim of this study was to determine OTA levels in the feed used in some poultry farms in Ismailia, Egypt and in organs of birds from those farms. Commercial ELISA kits were used to detect levels of OTA in poultry feed samples and main feed ingredients as well as its residues in bird’s tissues (Kidney, liver and muscles). Poultry feed samples were also tested for mycological contaminations. The most common commercial toxin binders were also evaluated in vitro. OTA concentration in poultry feed and ingredients ranged from 7.10-20.72 μg/kg. Soybean meal samples showed the lowest concentration, while rations formulated within the farm had the highest mean concentration. Producers using different toxin binders had a significant lower OTA concentration in their rations (p<0.05) as compared to those not using binders. OTA residues in different tissues were high in kidney and liver as compared to muscles. Asprigillus flavus was isolated from 80% of the examined feed samples. Different binders showed different abilities to bind OTA in vitro with highest binding capacity for yeast as compared to other commercially available binders.